DESIGNING DIGITAL STORYTELLING IN ENGLISH ONLINE LEARNING - Sri Yuliani; Dicki Hartanto (International Journal of Educational Management and Innovation, 2021)
The Covid-19 outbreak has led to many opportunities and chances for teachers and lecturers to create many media for online learning. The purpose of this research discusses 1) to design Digital storytelling in online learning, 2) to study the implementation of teaching English by using digital storytelling, and 3) to find out the practicality of digital storytelling for pre-service teacher students. This research uses d research development model developed by Alessi and Trollip (2001), which consists of three stages; the first stage is planning, the second stage designs, and third is development which focuses on designing digital storytelling to find more about the impact of digital storytelling as an online learning media process for English teaching material. The sample was 180 junior high students to get the needed analysis data, eight pre-service teacher students implemented the digital storytelling in the online classroom, and two evaluators to assess the appropriateness of digital storytelling to be used by pre-service teachers as it is found in this research that designing digital storytelling showed practically on how digital storytelling was designed, developed and applied in English class. The pre-service students successfully implemented digital storytelling, and the appropriateness was high, which can be used in the online teaching process